(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: Endoscopic Retrograde Cholangio Pancreatography (ERCP) is an established modality, mainly to treat pancreatico-biliary diseases. There are no comprehensive data about ERCP procedure from south-eastern part of Bangladesh. The aim of this study was to review the indications, cannulation success rate and complications of ERCP performed in a tertiary care centre of south-eastern Bangladesh. Materials and methods: In this retrospective cross-sectional study, 192 consecutive patients undergone ERCP between January 2015 to December 2019 were included to find out indications, success rate and complications of ERCP. Patients with any previous papillary intervention like papillotomy, sphincterotomy, stent placement, altered surgical anatomy were excluded. Data from computerized records of all of ERCP to a predesigned excel sheet were analyzed. Results: Among 192 patients, male was 79(41.15%) and female 113(58.85%) mean age 43.88 years with age range of 18 to 85 years. Significantly higher proportion of male had malignant biliary etiology compared to female (39.24 versus 10.62%). Cannulation success rate was 95.52%. Most of the therapeutic procedure done by classical sphincterotomy (88.02%) whereas precut needed in 11.98% procedures. Complete stone extraction was possible in 77.68% cases irrespective of stone sizes but 93.33% case of <10 mm sized stone were extracted at first ERCP. ERCP adverse events developed in 9.37% (n=18) patients and post ERCP pancreatitis was more frequent (5.21%). Conclusions: ERCP is a safe procedure though complication in our center was slightly higher than standard tertiary center. By proper selection of patients, using updated guidelines and accessories it can be done more safely onward. JCMCTA 2020 ; 31 (2) : 14-18